2013
DOI: 10.3109/17549507.2013.845691
|View full text |Cite
|
Sign up to set email alerts
|

Oral language supports early literacy: A pilot cluster randomized trial in disadvantaged schools

Abstract: This study examined the impact of teacher professional development aimed at improving the capacity of primary teachers in disadvantaged schools to strengthen children's expressive and receptive oral language skills and early literacy success in the first 2 years of school. Fourteen low-SES schools in Victoria, Australia were randomly allocated to a research (n = 8) or control arm (n = 6), resulting in an initial sample of 1254 students, (n = 602 in research arm and n = 652 in control arm). The intervention com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 28 publications
0
37
1
Order By: Relevance
“…Like Snow et al (2014) who highlighted the importance of speech pathologists in supporting teachers, this study acknowledges the importance of speech pathologists in supporting teachers and teacher assistants in primary schools. Future mixed methods research in this area will not only help to demonstrate the effectiveness of programs, such as PrepSTART in enhancing the oral language and literacy performance of children, but also provide a better understanding of the facilitators and barriers to implementing these programs in the classroom.…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…Like Snow et al (2014) who highlighted the importance of speech pathologists in supporting teachers, this study acknowledges the importance of speech pathologists in supporting teachers and teacher assistants in primary schools. Future mixed methods research in this area will not only help to demonstrate the effectiveness of programs, such as PrepSTART in enhancing the oral language and literacy performance of children, but also provide a better understanding of the facilitators and barriers to implementing these programs in the classroom.…”
Section: Resultsmentioning
confidence: 70%
“…Recent efforts to enhance the oral language and early literacy competence of young school-age children has focused on the role of the teacher in pre-school and primary school classrooms (Snow et al, 2014, Wilcox, Gray, Guimond, & Lafferty, 2011. For example, in the Teaching Early Literacy and Language program in pre-school settings, teachers received professional development, classroom support and mentoring to implement the curriculum (Wilcox et al, 2011).…”
Section: Oral Language Programs In School Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in all studies that included a training component and reported positive outcomes for children (see sections above) training was intensive and did not occur as an isolated training event. At Tier 1, successful professional development for education staff was at least 8 hours (in the Starling et al, 2012 study), but more often closer to 50-60 hours in Snow et al (2014) and studies in the meta-analysis by Markussen-Brown et al (2017) and accompanied by individual coaching or observation sessions. Tier 2 studies involved relatively intensive initial training (four days in Fricke et al, 2013;Bowyer-Crane et al, 2008) followed by regular (fortnightly), on-going training, support and monitoring for staff delivering programmes.…”
Section: Training For Parents or Education Staffmentioning
confidence: 98%